Environmental Management Influence for Shade Trees on the temperature Reduction of yhe building. - Khunthong, Thanawuth; ., . (International Journal of Engineering and Technology, 2018)
Thailand is located in a humid  tropical climate and near  the equator. Thus  the average air temperature is high throughout the  year.  Environmental factors   factors   such  as  the  sun,  wind  and  humidity affects   residential buildings especially, heat  from  the sun  is a main  factor,  which  leads  a problems of heat  inside  the  buildings (Prawewan Amornpong, 2001).  Therefore, Installling air conditioning inside  the buildings is the solution for this  problem. However, from  the  study  on  the  properties of  plants  it was  found  that  plants  are  effective in blocking  the   sun's   rays   as  well   as  effectively  maintaining  the   air   temperature  in  the   area   (Soontorn Boonyathikarn, 1999).  So, planting trees  to prevent the sunlight, as shade  to reduce  sun heat  in the buildings should   be  an  approach, which   could   be  adopted to  decrease the  use  of  air  conditioning and  also  energy consumption in buildings (Trungjai Buranasompob, 2000).  This  research aims  (1) to study  and  create  design guidelines on landscape models which  conforms to the environment of sunlight and wind  in the central region of Thailand and (2) to propose the guidelines on architectural landscape designs and plants’  setting  around the buildings in 8 directions; North  (N),  Northeast (NE),  East  (E),  Southeast (SE),  South  (S),  Southwe st (SW), West  (W)  and Northwest (NW).  The results   found  that the landscape model  included the setting  on plants  as shade  at all sides  of the building envelope during  08.00-17.00 PM  of the day  throughout the year.  These  can reduce  the  air  temperature of the  building envelope as well  as the  average temperature inside  the  buildings, this showed a decrease in temperature by as much  as 3.95°C or 13.478% compared with  the average exterior air temperature of the buildings throughout the year.